Reimagining the classroom creating new learning spaces and connecting with the world - Richards, Theodore (Hoboken, NJ Jossey-Bass, 2023)
"In Reimagining the Classroom: Creating New Learning Spaces and Connecting with the World, renowned educator Dr. Theodore Richards identifies the flaws and fissures in traditional approaches to teaching and learning, inspiring many to consider radical change. Dr. Richards takes a critical look at our education and reveals how impoverished our lives--and the lives of our children--have become. Our children are the pathway to reimagining our world and we are educating them to think of themselves as mere consumers rather than creators, to beware of the world rather than behold it, to think of themselves as isolated individuals rather than participants in communities and in the broader web of life. This is done not by telling our children what to think, but through a process of shared inquiry and exploration rooted in a renewed emphasis on our relationship to one another and the planet. The book is divided into two parts. The first offers the intellectual framework educators are seeking; it identifies specific problems with current approaches, offers an alternative vision and set of narratives, and then offers a new pedagogy to satisfy this vision. The second part of the book moves from the theoretical to the practical. Dr. Richards offers specific practices, activities, and ideas drawn from his decades of experience teaching children through the organization he founded, Wisdom Projects, Inc. Individual chapters address science and math; literature and fine arts; spirituality and mindfulness; practical arts; and justice and social-emotional learning. In each, Dr. Richards provides specific curricular examples--but more importantly, provides the steps and processes educators can use to create their own lessons"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Educational change -- United States; Education -- Aims and objectives -- United States